2017
DOI: 10.1021/acs.jpcc.7b05058
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Salt, Buffer, and Lipid Nature on Molecular Adsorption and Transport in Liposomes As Observed by Second Harmonic Generation

Abstract: It is of great importance to interrogate the impact of local environment on the transport of small molecules across lipid bilayers, as they are key to the function and capabilities of eukaryotic cells and liposome-based delivery systems. Herein are described real-time studies of the molecular adsorption and transport kinetics of positively charged small-molecule organic dyes at the surface of liposomes under different buffer and salt conditions, made possible by application of second harmonic generation (SHG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 68 publications
16
70
0
Order By: Relevance
“…SHG is dipole forbidden in centrosymmetric media, like bulk solution, but can be generated at the surface of nanoparticles where the symmetry is broken. Recently, SHG has been used as an accurate method to determine molecular adsorption and chemical reactions at nanoparticle surfaces, ion‐transport processes in liposomes, and the release of oligonucleotides from the surface of plasmonic nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…SHG is dipole forbidden in centrosymmetric media, like bulk solution, but can be generated at the surface of nanoparticles where the symmetry is broken. Recently, SHG has been used as an accurate method to determine molecular adsorption and chemical reactions at nanoparticle surfaces, ion‐transport processes in liposomes, and the release of oligonucleotides from the surface of plasmonic nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…The SHG signal from the molecular dye dissolved in water is due to incoherent hyper-Rayleigh scattering (HRS), where the SHG signal is proportional to the molecular concentration. [52][53][54][55][56][57][58] Enhanced SHG from the nanoGUMBOS as compared with the molecular dye is attributed primarily to the increased size. To a first approximation, the SHG signal is expected to scale as the radius to the sixth power for small nanoparticles, 51,59 although many other factors are important including the molecular nonlinear susceptibilities and angular scattering distributions.…”
Section: Resultsmentioning
confidence: 99%
“…While SHG is a coherent process for a single nanoparticle, the measured SHG signal from a colloidal nanoparticle sample is an incoherent sum of the nanoparticles in the laser focus such that the total SHG signal is linearly proportional to the nanoparticle concentration. 50,51,[56][57][58] The nanoGUMBOS also have a higher extinction at 800 nm as compared with the BG molecule and the gold nanospheres, causing some single-photon resonance enhancement in the nonlinear spectroscopy. Local ordering of the BG molecules in the nanoGUMBOS due to aggregation and π-π stacking may also occur causing orientations that are not isotropically distributed, leading to an additional source of increased SHG signals.…”
Section: Resultsmentioning
confidence: 99%
“…It was expected that the rate of transport across the CM shouldb es imilar to those obtained from prior liposome-based studies. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In both cases, the molecular probe has to directly diffusea cross the lipid bilayer.S till, the deduced average moleculart ransport rate for the bacterial CM is found to be an order of magnitude slower compared to unilamellar liposomes (ca. 10 À3 s À1 )w hose lipid composition was homogeneous.…”
Section: A Mg Adsorption and Transport Through Individual Membranes mentioning
confidence: 99%
“…Following this demonstration,anumber of studies have since examined the effects of lipid composition and av ariety of environmental factorso nt he propensity and characteristics of molecular transport across membranes in model liposome systems. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The studies on liposomes suggested the feasibility that SHS could be used for monitoring molecular transport across membranesi nl iving biological cells. Indeed, in 2010, our laboratory reportedt he first demonstration that SHS could be applied to study molecular transport across membranes in living cells.…”
Section: Introductionmentioning
confidence: 99%